Hybrid anion exchanger for trace phosphate removal from water and wastewater - Blaney, Lee M.; Cinar, Suna; SenGupta, Arup K. (Water research (Oxford), 2007)
Throughout recent decades, the wastewater treatment industry has identified the discharge of nutrients, including phosphates and nitrates, into waterways as a risk to natural environments due to the serious effects of eutrophication. For this reason, new tertiary treatment processes have abounded; these processes generally utilize physico–chemical and biological methods to remove nutrients from secondary wastewaters. The disadvantages of such methods involve larger reactor volumes, operating costs, and waste sludge production; furthermore, complete nutrient removal is unattainable due to thermodynamic and kinetic limitations. The subject study presents the development and performance of a new phosphate-selective sorbent, referred to as hybrid anion exchanger or HAIX. HAIX combines durability and mechanical strength of polymeric anion exchange resins with high sorption affinity of hydrated ferric oxide (HFO) toward phosphate. HAIX is essentially a polymeric anion exchanger within which HFO nanoparticles have been dispersed irreversibly. Laboratory studies show that HAIX selectively removes phosphate from the background of much higher concentrations of competing sulfate, chloride and bicarbonate anions due to the combined presence of Coulombic and Lewis acid–base interactions. Experimental results demonstrate that HAIX's phosphate–sulfate separation factor is over two orders of magnitude greater than that of currently available commercial ion exchange resins. Additionally, optimal HAIX performance occurs at typical secondary wastewater pH conditions i.e., around 7.5. HAIX is amenable to efficient regeneration and reuse with no noticeable loss in capacity.